IMPLEMENTASI RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA PENCABULAN TERHADAP ANAK OLEH KEPOLISIAN SEKTOR MANDAU - Fitri, Defira Ratu Sari; Artina, Dessy; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Increasing crime in Indonesia results in the emergence of various modus operandi in the occurrence of criminal acts. In addition, the lack of public knowledge about criminal law causes one to be a victim of a criminal act or a criminal offender. One of the perpetrators is a criminal act of abuse. The offense of abuse is a criminal offense and violates decency and decency. Restorative Justice is an alternative or other way of criminal justice by putting forward the integration approach of the perpetrator on the one hand and the victim / community on the other as a unity to seek. Restorative Justice is the concept of completion on the effort of retaining or repairing / restoring damaged condition or condition as result of a crime. The ones to be restored / repaired / restored are victims, perpetrators of criminal acts, and other damages caused by criminal acts in the community. Therefore, it needs to be studied simultaneously about the First Implementation of Restorative Justice in the settlement of crime against children in Police Sector Mandau. Second, the role of the Mandau Sector Police in settling criminal acts of child abuse.The type of research used in the writing of this law is the study of sociological law. Population and sample are all parties related to the problem studied in this research, data source used, primary data, secondary data, and tertiary data, data collecting technique in this research by interview and literature study.The results showed that there are two main points that can be concluded. First, Restorative Justice can repair damages or losses, restore the situation as it was, and restore the quality of the relationships of the parties involved and related. Not all cases of abusive offenses can be resolved with penal mediation. Rather there must be a selection of crimes that have been committed or are being dealt with. So if it is done with the situation of the victim full of injuries, the recidivists and the occurrence of intercourse, then can not be settled by mediation but done according to the applicable law. Second, the role of the Mandau Sector Police in the settlement of criminal acts of abuses against children, such as Pre-emtive Action and Pre-Ventive (non-penal) Action. The author's suggestion Firstly, the police should improve and maximize its performance in order to implement the protection of the rights of victims of the crime of child abuse in accordance with Law Number 35 Year 2014 regarding the amendment to Law Number 23 Year 2002 regarding Child Protection. Second, For the government so that the investigator / auxiliary investigator to immediately issue a Government Regulation or Legislation Law which is the legal basis for investigators in the application of the concept of Restorative Justice settlement of criminal acts of child abuse.Keywords: Implementation - Restorative Justice - Obscene - Underage